Aggression in children with autism spectrum disorders and a clinic-referred comparison group. (April 2015) - Farmer, Cristan; Butter, Eric; Mazurek, Micah O; Cowan, Charles; Lainhart, Janet; Cook, Edwin H; DeWitt, Mary Beth; Aman, Michael
A gap exists in the literature regarding aggression in autism spectrum disorders and how this behavior compares to other groups. In this multisite study, the Children's Scale for Hostility and Aggression: Reactive/Proactive and the Aggression subscale of the Child Behavior Checklist were rated for 414 children with autism spectrum disorder (autistic disorder, 69%; pervasive developmental disorder not otherwise specified, 24%; Asperger's disorder, 7%) and 243 clinic-referred children without autism spectrum disorder, aged 1–21 years (mean age about 7 years). Participants were not selected for aggressive behavior. Relative to the comparison group, children with autism spectrum disorder were reported to have less aggression and were more likely to be rated as reactive rather than proactive. Among all subjects, sex was not associated with aggression; higher IQ/adaptive behavior and older age were associated with more sophisticated types of aggression, while lower scores on IQ, adaptive behavior, and communication measures were associated with more physical aggression. The interaction between demographic variables and diagnosis was significant only for age: younger but not older children with autism spectrum disorder showed less aggression than clinic-referred controls.